Ressignificação da identidade social de pessoas com deficiência através da prática de esporte: possibilidade e percursos - SOUZA, Aparecida Carina Alves de (2014)
The dissertation focuses on the trajectory of some people with disabilities who become athletes practicing athletics in order to uncover the relationship they established this practice and how they fit into society. Reflects more specifically on the role and importance of practicing sport in social dynamics experienced by ten (10) athletes linked to SUPERAR Institute, taking it as a tool to contribute to the reinvention of identity and, as such, to boost social inclusion. Discusses a social group with dimensions and particular traits and reframing that attach to their social identity. Includes, in addition to the experiences that are established in their lives before and after sports practice, ways of seeing, thinking and feeling, from the built collected by semistructured interviews and narratives, defining itself as well as tax the line of research Representation of Historicity, memory and speech. When considering the meager amount of references regarding the social identity of people with disabilities to participate in sport, not only intends to contribute to prove that this is an important fact that cannot be disregarded, but open other possibilities, either by allowing the systematization of knowledge that permeates the universe, is to reveal routes to be followed in the process of consolidation of power as people with disabilities in the Paralympic Games.